A Historical Analysis of the Co-evolution of Gasoline Octane Number and Spark-Ignition Engines - Splitter, Derek; Pawlowski, Alexander; Wagner, Robert (Frontiers in Mechanical Engineering, 2016)
In this work, the authors reviewed engine, vehicle, and fuel data since 1925 to examine the historical and recent coupling of compression ratio and fuel antiknock properties (i.e., octane number) in the U.S. light-duty vehicle market. The analysis identified historical time frames and trends and illustrated how three factors—consumer preferences, technical capabilities, and regulatory legislation—affect personal mobility. Data showed that over many decades these three factors have a complex and time-sensitive interplay. Long-term trends in the data were identified where interaction and evolution between all three factors were observed. Specifically, transportation efficiency per unit power (gal/ton-mi/hp) was found to be a good metric to integrate technical, societal, and regulatory effects into the evolutional pathway of personal mobility. From this framework, discussions of future evolutionary changes to personal mobility are also presented, with a focus centered on how increasing fuel octane number can help to enable sustained improvement in transportation efficiency per unit power.